A homogenized approach to classify advanced gastric cancer patients with limited and adequate number of pathologically examined lymph nodes. Issue 1 (10th June 2019) - Seeruttun, Sharvesh Raj; Xu, Lipu; Wang, Fangwei; Yi, Xiaodong; Fang, Cheng; Liu, Zhimin; Wang, Wei; Zhou, Zhiwei
Abstract: Background: The prognosis of gastric cancer patients with a limited number of pathologically examined lymph nodes (eLN, < 16) is dismal compared to those with adequately eLN (≥ 16), yet they are still classified within the same subgroups using the American Joint Committee on Cancer (AJCC) staging system. We aimed at formulating an easy‐to‐adopt and clinically reliable stratification approach to homogenize the classification for these two categories of patients. Methods: Patients staged according to the 8th AJCC pathological nodal (N) and tumor‐node‐metastasis (TNM) classification were stratified into a Limited and Adequate eLN cohort based on their number of pathologically examined LNs. The statistical differences between the 5‐year overall survival (OS) rates of both cohorts were determined and based on which, patients from the Limited eLN cohort were re‐classified to a proposed modified nodal (N′) and TNM (TN′M) classification, by matching their survival rates with those of the Adequate eLN cohort. The prognostic performance of the N′ and TN′M classification was then compared to a formulated lymph‐node‐ratio‐based nodal classification, in addition to the 8th AJCC N and TNM classification. Results: Significant heterogeneous differences in 5‐year OS between patients from the Limited and Adequate eLN cohort of the same nodal subgroups were identified (all P < 0.001). However, no significant differences in 5‐year OS were observed between the subgroups N0, N1, N2, and N3a of the Limited eLN cohort when compared with N1, N2, N3a, and N3b from the Adequate eLN cohort, respectively ( P = 0.853, 0.476, 0.114, and 0.230, respectively). A novel approach was formulated in which only patients from the Limited eLN cohort were re‐classified to one higher nodal subgroup, denoted as the N′ classification. This re‐classification demonstrated superior stratifying and prognostic ability as compared to the 8th AJCC N and lymph‐node‐ratio classification (Akaike information criterion values [AIC]: 12, 276 vs. 12, 358 vs. 12, 283, respectively). The TN′M classification also demonstrated superior prognostic ability as compared to the 8th AJCC TNM classification (AIC value: 12, 252 vs. 12, 312). Conclusion: The proposed lymph node classification approach provides a clinically practical and reliable technique to homogeneously classify cohorts of gastric cancer patients with limited and adequate number of pathologically examined lymph nodes.